2009
DOI: 10.1161/circep.109.867978
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Arrhythmias After Lung Transplantation

Abstract: Background-Atrial arrhythmias (AAs) including atrial fibrillation (AF) and atrial tachycardia (AT) are often observed after cardiothoracic surgery. Our aim was to evaluate the prevalence and mechanism of AAs after lung transplantation. Methods and Results-All patients (nϭ127) after bilateral sequential lung transplantation followed at our institution over 20 years were included. All patients received postoperative rhythm monitoring and clinic visits with ECG at 1, 3, 6, and 12 months, or as needed. AAs occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…9,[12][13][14] It is the second largest series after that of Mason et al, 13 which reported a lower incidence of 20%. Dizon et al 12 compared the incidence of AF after lung or heart transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[12][13][14] It is the second largest series after that of Mason et al, 13 which reported a lower incidence of 20%. Dizon et al 12 compared the incidence of AF after lung or heart transplant.…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14] Only 1 series assessed the independent role of identified risk factors. 9 Concurrent postoperative complications may affect to a greater extent the short-term prognosis of these patients.…”
Section: Clinical Perspective On P 67mentioning
confidence: 99%
“…See et al also described 4 patients who underwent electrophysiological study, with 1 CTI, 2 left-sided macroreentrant tachycardia, and 1 focal atrial tachycardia being diagnosed. 2 Catheter ablation may indeed be useful in this category of LT patients with recurrent AFL.…”
Section: Mortalitymentioning
confidence: 99%
“…An interesting subset of lung transplant patients may have atrial tachycardias using donor-to-recipient conduction across an anastomotic line. This has been supported by 2 case reports [3,15] but disputed by some studies including a series of 25 patients in whom electrophysiological mapping showed that all PV antral arrhythmias arose from recipient not donor myocardium [16]. …”
mentioning
confidence: 95%
“…Atrial arrhythmias in the early post-operative period are mostly AF, whereas late arrhythmias are mostly atrial tachycardias (AT) [3]. It is unclear if these phenotypes reflect differences in the physiological milieu, e.g., higher autonomic tone or inflammation in the early post-operative period vs. the formation of structural barriers enabling subsequent stable re-entrant or focal atrial tachycardias in the later period.…”
mentioning
confidence: 99%